1976
DOI: 10.1080/14640747608400557
|View full text |Cite
|
Sign up to set email alerts
|

An “Across-the-Board” Modality Effect in Immediate Serial Recall

Abstract: A serial recall experiment comparing visual and auditory presentation is reported which demonstrates that, under certain conditions, there is an auditory advantage in the pre-recency (1–6) as well as the recency (7–8) serial positions. Presentation modality was combined factorially with five levels of a concurrent writing task, which had to be completed for each to-be-remembered digit during presentation: NC, no concurrent task; XX, writing two crosses; DX, writing each digit followed by a cross; XD, the conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
21
1
1

Year Published

1978
1978
1999
1999

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 58 publications
4
21
1
1
Order By: Relevance
“…It should be noted, however, that through-list modality effects have been reported for recall tasks. Greene (1985), Routh (1976), and J. M. Gardiner, Gregg, and M. M. Gardiner (1984) have reported through-list modality effects in serial recall, and J. M. Gardiner et al (1984) have found them in free recall.…”
Section: Resultsmentioning
confidence: 98%
“…It should be noted, however, that through-list modality effects have been reported for recall tasks. Greene (1985), Routh (1976), and J. M. Gardiner, Gregg, and M. M. Gardiner (1984) have reported through-list modality effects in serial recall, and J. M. Gardiner et al (1984) have found them in free recall.…”
Section: Resultsmentioning
confidence: 98%
“…3 The specifics of the masking process in the auditory case have not been fmally determined, but a detailed description of some possible mechanisms can be found in Crowder (1978a). In addition, the suffix is known to have other "across-the-board" effects (see Balota & Engle, 1981;Penney, 1985;Routh, 1976) that also will not be treated here. It is sufficient simply to note that suffixes may potentially interfere with both modalityindependent and modality-dependent features, but only the latter are primarily responsible for the selective impairment of recency.…”
Section: A Framework For Recency 347mentioning
confidence: 99%
“…Using a probed-recall task, Murdock (1967) found that the modality effect extended throughout a 10-item list as long as both probe and target were auditory, and Penney (1982b, Experiment 2) found a small suffix effect of similar extent. Routh (1976) obtained the auditory superiority throughout an 8-item list when subjects engaged in a concurrent writing task. If the PAS is hypothesized to contain information about only 1 or at most 2 items, it is difficult to see how the PAS model can account for suffix and modality effects that extend over 4 to 9 items.…”
Section: Alternate Accounts Of Modality Effectsmentioning
confidence: 99%